Power Inequalities for the Numerical Radius of a Product of Two Operators in Hilbert Spaces - Dragomir, S. S. (Sarajevo journal of mathematics, 2024)
Some power inequalities for the numerical radius of a product of two operators in Hilbert spaces with applications for commutators and self-commutators are given.